Rethinking financial behaviour: Rationality and resistance in the financialization of everyday life - Agunsoye, Ariane (Bristol Bristol University Press, 2025)
Pension policy in the UK and US is designed on the assumption that people make informed financial decisions, consistently invest in pensions and manage diverse portfolios. Deviating from this is often deemed irresponsible and irrational. However, this assumption overlooks uncontrollable factors like caring duties, employment breaks or income limitations.